SKIN CANCER IN CHILDREN WITH XERODERMA PIGMENTOSUM - Maria Meildi; Monty Priosodewo Soemitro; Maman Abdurahman; Raden Yohana; Kiki Akhmad Rizki; Hermin Aminah Usman (Jurnal Health Sains, 2023)
Introduction: Xeroderma pigmentosum) is a rare disease, inherited in an autosomal recessive manner with disturbances in the repair of deoxyribonucleic acid (DNA) which often occur in malignancy. Irreversible DNA lesions and mutations also occur in the genes which regulate skin cancer development in Xeroderma Pigmentosum. Purpose: To explain the signs, symptoms, and management of  skin cancer Xeroderma Pigmentosum. Case Report : A 6 year old girl with basal cell carcinoma arising from Xeroderma pigmentosum.  The histopathological picture of the left nasolabial biopsy preparation was found to show basal cell carcinoma (BCC). The patient was treated with 5FU administration and were followed after 6 week In the second patient, a 3 year old boy, squamous cell carcinoma in the oocipital area. From the histopathological picture, moderately differentiated squamous cell carcinoma on the left frontalis occipital dextra and corresponds to mottled hypermegrance on the parietal dextra. In this patient, a wide excision of the occipital lump was performed and the defect was closed with a full-thickness skin graft. Provided education to the parents of both patients for direct prevention of sun exposure by using sunscreen/hats. Discussion and Conclusion: Xeroderma Pigmentosum patients who are Xeroderma Pigmentosum  to ultraviolet radiation (UV) can result in the development of highly cancerous lesions consisting of squamous cell carcinoma (SCC), basal cell carcinoma (BCC), and malignant melanoma (MM). Clinical management of Xeroderma Pigmentosum includes sun avoidance, minimizing UV eXeroderma Pigmentosumosure, early detection, skin lesions, and genetic counseling. Topical application of 5-fluorouracil or imiquimod is used for premalignant lesions, and surgical excision is performed for malignant neoplasms of the skin, tongue, eyelids, conjunctiva, and cornea.